2021
DOI: 10.1111/ejn.15208
|View full text |Cite
|
Sign up to set email alerts
|

No behavioural evidence for rhythmic facilitation of perceptual discrimination

Abstract: It has been hypothesized that internal oscillations can synchronize (i.e., entrain) to external environmental rhythms, thereby facilitating perception and behaviour. To date, evidence for the link between the phase of neural oscillations and behaviour has been scarce and contradictory; moreover, it remains an open question whether the brain can use this tentative mechanism for active temporal prediction. In our present study, we conducted a series of auditory pitch discrimination tasks with 181 healthy partici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 65 publications
(74 reference statements)
1
41
1
Order By: Relevance
“…These effects might be associated with entrainment, in which low-frequency neural oscillations in connection with fluctuations between periods of high and low neural sensitivity to the input and become phase-aligned to the external rhythmic stream such that periods of high sensitivity coincide with on-beat times of rhythmic stimuli ( Jones, 1976 ; Large and Jones, 1999 ; Barnes and Jones, 2000 ; Schroeder and Lakatos, 2009 ; Breska and Deouell, 2016 ). A handful of studies failed to find the rhythmic behavioral benefits ( Benwell et al, 2017 ; Ruzzoli et al, 2019 ; Vigué-Guix et al, 2020 ; Lin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These effects might be associated with entrainment, in which low-frequency neural oscillations in connection with fluctuations between periods of high and low neural sensitivity to the input and become phase-aligned to the external rhythmic stream such that periods of high sensitivity coincide with on-beat times of rhythmic stimuli ( Jones, 1976 ; Large and Jones, 1999 ; Barnes and Jones, 2000 ; Schroeder and Lakatos, 2009 ; Breska and Deouell, 2016 ). A handful of studies failed to find the rhythmic behavioral benefits ( Benwell et al, 2017 ; Ruzzoli et al, 2019 ; Vigué-Guix et al, 2020 ; Lin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence for persistent entrainment is sparse. Some behavioral studies have shown persistent effects of rhythmic input on subsequent responses (Hickok, Farahbod, & Saberi, 2015;Jones et al, 2002), though this has sometimes proven hard to replicate (Bauer, Jaeger, Thorne, Bendixen, & Debener, 2015;Lin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies investigating rhythms in behavior has been growing in recent years (VanRullen, 2016a). However, different methods have been used to analyses these data, making the comparison between studies difficult, and concerns over reproducibility have been raised (Lin et al, 2021; Sun et al, 2021; van der Werf et al, 2021). Moreover, it is not clear which of these methods is more optimal to maximize the detection of true rhythms while minimizing the chance of false discoveries.…”
Section: Discussionmentioning
confidence: 99%